New test for the diagnosis of bacterial endophthalmitis. Issue 8 (10th February 2009) - Goldschmidt, P; Degorge, S; Benallaoua, D; Basli, E; Batellier, L; Boutboul, S; Allouch, C; Borderie, V; Laroche, L; Chaumeil, C
Abstract : Background: Diagnosis of bacterial endophthalmitis (BE) often fails due to: (1) insufficient volumes of vitreous fluid (VF) and aqueous humour (AH); (2) lack of sensitivity of culture; (3) antibiotic treatments; (4) polymerase chain reaction (PCR) cross-contamination; and (5) limitations on the interpretation of the real-time PCR melting curve. We developed a fast real-time (f-real-t) PCR to improve the performance of the laboratory diagnosis of BE. Methods: The following samples were processed after adding an internal control: phosphate buffered saline (PBS); VF, AH and cell suspensions spiked with Bacteria ( Bac ); VF and AH from patients with endophthalmitis; and VF and AH from non-infective patients. DNA was extracted (MagNA Pure®) and added to four tubes containing selected primers and probes for the identification and quantification of all Bac and eight genera by f-real-t PCR. Diagnostic performances based on direct microscopic examination, culture and f-real-t PCR were compared. Results: The f-real-t PCR detected at least 0.01 colony-forming units (CFU) of Bac /μl with no cross-reactivity with fungi. Correlation with culture-positive results was 100%. Sixty per cent of BE samples tested culture-positive, but f-real-t PCR tested positive for 90%. Samples from non-infective cases were negative. Conclusion: The f-real-t PCR detected and quantified Bac, Staphylococci, Streptococci, Haemophilus, Pseudomonas, Enterobacteria, Acinetobacter, Propionibacteriacae and Corynebacteria in one run. Cultures required several hours to days (with a non-negligible number of false-negative results) and the f-real-t PCR was completed in 90 min. The f-real-t PCR is presented as a new tool for the diagnosis of BE: its usefulness requires validation with larger series of samples.